Fusarium An Overview of the Genus - Mahyar Mirmajlessi, Seyed (IntechOpen, 2022)
Fusarium is a large cosmopolitan genus of ascomycete fungi that are among the most important toxigenic plant pathogens causing seed and soil-borne diseases in a wide variety of agricultural crops worldwide. Fusarium species are broadly distributed in soil, root and plant tissues, and other organic substrates. Almost all species are able to generate mycotoxins, as secondary metabolites, that cause different physiological responses in plants. This book provides an overview of recent research on Fusarium species in the fields of metabolites, pathogenicity, plant-pathogen interactions, and management strategies in agricultural practices.